Drones, force and law European perspectives - Dunn, David 19XX-; Wheeler, Nicholas J. 1962-; Davies, Jack; Sabur, Zeenat (Cambridge elements, 2023)
The central argument set out in this Element is that the combination of a perceived radical change in the threat environment post 9/11, and the new capabilities afforded by the long silent reach of the drone, have put pressure on the previously accepted legal frameworks justifying the use of force. This has resulted in disagreements - both articulated and unarticulated - in how the Western allies should respond to both the legal and operational innovations in the use of force that drones have catalysed. The Element focuses on the responses of the UK, France, and Germany to these developments in the context of the changing US approach to the use of force. Locating itself at the interface of international law and politics, this is the first attempt to look at the interplay between technological innovations, legal justifications, and inter-alliance politics in the context of the use of armed drones